OPTIMALISASI PRODUKSI TANAMAN TERUNG DENGAN PEMANFAATAN MULSA ORGANIK - Villa Afria sari; Rita Hartati; cukri rahmi niani (Jurnal Optimalisasi, 2019)
This study to determine the use of organic mulch on eggplant production. This research was carried out in the garden of kemumu Hilir Village, Labuhan Haji Timur Disrtict,South aceh Regency. The design used was RAK with the treatment of organic mulch iesugarcane bagasse, rice straw mulch and reeds. The result showe that best eggplant production was found in the treatment of straw mulch, namely the number of fruits (1,506 pieces), fruit length (18,814cm) and the average weight per fruit (112,763gram).